2008
DOI: 10.1530/rep-07-0376
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate cluster analysis to study motility activation of Solea senegalensis spermatozoa: a model for marine teleosts

Abstract: Computer-assisted sperm analysis (CASA) and clustering analysis have enabled to study sperm subpopulations in mammals, but their use in fish sperm has been limited. We have used spermatozoa from Senegalese sole (Solea senegalensis) as a model for subpopulation analysis in teleostei using two different activating solutions. Semen from six males was activated using 1100 mOsm/kg solutions: artificial seawater (ASW) or sucrose solution (SUC). Motility was acquired at 15, 30, 45, and 60 s post-activation. CASA para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 40 publications
8
47
0
Order By: Relevance
“…This approach 83 promises a deeper understanding of the inner dynamics of the sperm sample, since its intrinsic 84 heterogeneity is taken into account (Holt and Harrison, 2002;Martinez-Pastor et al, 2005a). 85 Subpopulation analysis has been applied in a few studies in fishes: Sole fish (Solea senegalensis) (Beirão 86 et al, 2009;Martínez-Pastor et al, 2008), sea bream (Sparus aurata) (Beirão et al, 2011), three-spined 87 stickleback (Gasterosteus aculeatus) (Le Comber et al, 2004) and steelhead (Oncorhynchus mykiss) 88 (Kanuga et al, 2012). In these studies, 3-4 subpopulations of spermatozoa were identified, one of them 89 being defined as more desirable (containing fast and linearly motile cells) (Beirão et al, 2009; 90 Martínez-Pastor et al, 2008).…”
Section: Csiro Publishingmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach 83 promises a deeper understanding of the inner dynamics of the sperm sample, since its intrinsic 84 heterogeneity is taken into account (Holt and Harrison, 2002;Martinez-Pastor et al, 2005a). 85 Subpopulation analysis has been applied in a few studies in fishes: Sole fish (Solea senegalensis) (Beirão 86 et al, 2009;Martínez-Pastor et al, 2008), sea bream (Sparus aurata) (Beirão et al, 2011), three-spined 87 stickleback (Gasterosteus aculeatus) (Le Comber et al, 2004) and steelhead (Oncorhynchus mykiss) 88 (Kanuga et al, 2012). In these studies, 3-4 subpopulations of spermatozoa were identified, one of them 89 being defined as more desirable (containing fast and linearly motile cells) (Beirão et al, 2009; 90 Martínez-Pastor et al, 2008).…”
Section: Csiro Publishingmentioning
confidence: 99%
“…In the present study, we have adapted an unsupervised cluster analysis from previous studies on 92 sperm classification (Martinez-Pastor et al, 2005b;Martínez-Pastor et al, 2008; Domínguez-Rebolledo 93 et al, 2011), in order to discover the subpopulation structure of European eel sperm, and to apply this 94 information to improve our knowledge on the effect of thermal and hormonal treatments on the 95 spermatogenesis and sperm quality in this species. Since there is no prior knowledge about the 96 subpopulational structure of eel spermatozoa, we performed a previous cluster analysis on sperm samples 97 obtained following a standard protocol, at different times after activation.…”
Section: Csiro Publishingmentioning
confidence: 99%
“…Motility parameters, obtained from a CASA system, can be represented using Chernoff faces [Martínez-Pastor et al 2008]. However, to our knowledge, this is the first time that Chernoff faces were used to represent individual measurements obtained from a CASA system.…”
Section: Discussionmentioning
confidence: 99%
“…Representation of multivariate data in the form of Chernoff faces has been used to detect outliers [Johnson 1998] and to describe data obtained from CASA systems [Martínez-Pastor et al 2008;Martínez-Pastor et al 2011]. In addition, multivariate statistics can be used to reduce the dimensionality of a dataset and to cluster observations based on similarities.…”
Section: Introductionmentioning
confidence: 99%
“…A recent development has been the application of cluster analysis to such data to reveal subpopulations with differing overall characteristics within the sample (42). By such means, subpopulations expressing hyperactive motility or rapid forward motion can be detected (64).…”
Section: Motilitymentioning
confidence: 99%